CCTV Monitoring System Development for Safety Management and Privacy in Manufacturing Site - Han, Ji Hee; Ok, Sang Hun; Song, Kyu; Jang, Dong Young (Journal of the Korean Society of Manufacturing Technology Engineers, 2017)
CCTV image processing techniques have been developed for safety management in manufacturing sites. However, CCTV growth has become a social problem for video surveillance with regard to privacy. This study aims to manage the safety system efficiently and protect privacy simultaneously. In this study, the CCTV monitoring system is composed of five steps (accident monitoring, detection, notification, management, restoration). De-identified image is observed when we are in a normal situation. De-identified image changes to identified image when it detects an accident. As soon as it detects an accident, the accident information is sent to the safety administrator. Then the administrator could conduct safety measures. Afterward, accumulated accident data could be used for statistical data that could be utilized as analyzing expecting accident. KCI Citation Count: 0